Damage detection of carbon fibers in filament winding machines using an electrical resistance method - TOPTAŞ, ERSİN; AKKUŞ, NİHAT (SPRINGER LONDON LTD, 2017)
The aim of this research project is to detect the presence of fiber damage which occurs during the pretensioning of carbon fibers during the Filament Winding (FW) manufacturing process. The property of electrical conductivity of the carbon fibers was investigated to determine the existence and level of fiber damage. An experimental system was designed and developed to simulate the pretension system of a FW machine and measure the electrical change of broken fibers during the winding process. Toray T1000G-12K type of carbon fiber was used in the experimental stage of this research project. The damaged fibers were later used to obtain tension test pieces to evaluate the amount of damage which was caused by the pretensioning unit. The tension test was carried out according to ASTM 4018-99. The results demonstrated that the electrical conductive property of carbon fibers can be effectively used to evaluate the damage which occurs during the pretensioning in the FW process.
Keywords: Carbon fiber damage; Filament winding; Fiber pretension; Electrical conductivity; Continuous fiber; CFRP; COMPOSITES; BEHAVIOR; TENSION